Evaluation of carbohydrate‐to‐lipid ratio in diets supplemented with Bacillus subtilis probiotic strain on growth performance, body composition and digestibility in juvenile white seabass (Atractoscion nobilis, Ayres 1860). (17th November 2014) - López, Lus M; Olmos Soto, Jorge; Trejo Escamilla, Idaly; Flores Ibarra, Maricela; Ochoa, Leonel; Drawbridge, Mark; Peres, Helena
Abstract: This study aimed to evaluate the effect of increasing the carbohydrate to lipid ratio in diets supplemented with Bacillus subtilis in white seabass ( Atractoscion nobilis ) juveniles on digestibility, growth performance, feed utilization efficiency and tissue composition. Four experimental isoenergetic and isoproteic diets supplemented with B. subtilis were formulated with increasing starch to lipid ratios (g/g) of 10:19; 14:17; 18:15 and 22:13 (diets PD10, PD14, PD18 and PD22 respectively). A negative control diet for B. subtilis supplementation was also formulated to be similar to diet PD10 (diet CD10). Each experimental diet was fed to triplicate groups of 20 fish per tank (IBW: 9.5 g), three times a day, to apparent satiation, for 60 days. Supplementation with B. subtilis, of the low starch‐high lipid diet (10:19), significantly enhanced the overall growth performance, digestibility and feed efficiency. Moreover, the increase in starch to lipid ratio, in supplemented probiotic diets, significantly increased growth performance, feed intake, feed utilization efficiency and protein and energy digestibility, being maximum for the highest dietary starch to lipid level. Lipid content of whole body, muscle and liver and hepatosomatic index significantly increased with the increase in starch to lipid ratio. The results of this study indicate that B. subtilis supplementation significantly enhanced growth performance, digestibility and feed utilization of low starch‐high lipid diet. However, further improvement of growth performance and feed utilization efficiency may be achieved combining B. subtilis supplementation with increased dietary starch to lipid ratio to 22:13.